Convergence and Stability of a Perturbed Mann Iterative Algorithm with Errors for a System of Generalized Variational-Like Inclusion Problems in \(q\)-uniformly smooth Banach Spaces - Kim, Jong Kyu; Bhat, Mohammad Iqbal; Shafi, Sumeera (Communications in Mathematics and Applications, 2021)
In this paper, we introduce a class of \({\cal H}(·,·)\)-\(φ\)-\(η\)-accretive operators in a real \(q\)-uniformly smooth Banach space. We define the resolvent operator associated with \({\cal H}(·,·)\)-\(φ\)-\(η\)-accretive operator and prove that it is single-valued and Lipschitz continuous. Moreover, we propose a perturbed Mann iterative method with errors for approximating the solution of the system of generalized variational-like inclusion problems and discuss the convergence and stability of the iterative sequences generated by the algorithm. Our results presented in this paper generalize and unify many known results in the literature.